Dermatoglyphics and Its Importance in Oral Precancerous and Cancerous Lesions - Systematic Review: Life Sciences-Medicine - Gunasekaran, Vinothini; Elangovan, Elavarasi; Nagarajan, Prithiviraj; Deepak Jeyaraj, John Hearty; Thangarasu, Rajan (International Journal of Life Science and Pharma Research, 2022)
Dermatoglyphics, the study of palm prints and fingerprints, is currently a precious method for the early detection of premalignant lesions, dental caries, systemic disorders, hereditary diseases, and syndromes. Palmar dermatoglyphics can indicate the development of potentially malignant lesions and help identify people at high risk of developing oral submucous fibrosis (OSMF) , and oral squamous cell carcinoma (OSSC), which cause panic and hold an excessively high ranking as killers. Another important condition that has become a major public health issue in the South Indian population is oral submucous fibrosis (OSMF), which is correlated with genetic abnormalities and is used in biomedical studies. Similarly, anthropologists and medical professionals have long found the study of the human hand fascinating, as have psychologists, novelists, artists, and chiromancers. Fingerprints do not change when the body decays, just as they change from birth to death. Our systematic review aims to assess the correlation between dermatoglyphics and oral precancerous and cancerous lesions in the human population and to investigate the embryogenesis and topology of dermatoglyphics, emphasizing the many types of research involving dermatoglyphics in many disciplines of medicine and dentistry. In our systematic review, we have collected many review papers using databases including PubMed, Medline, Scopus, Embase, and the Web of Science to determine the importance of dermatoglyphics in oral precancerous and cancerous lesions. The data from our systematic review showed a link between oral precancerous and cancerous lesions, which suggests that dermatoglyphics could be used to find precancerous and cancerous lesions in the oral cavity early.